Teachers’ Collegiality: A Professional Development Tool for Algerian Novice Teachers - Guellouma Rima; Bilouk Imene (Acta Educationis Generalis)
Introduction: This research aims to discover the role of collegiality, as one of the internationally recognized tools for continuous professional development, in the professional growth journey of both novices and experts to give an insight into how effective, forming and maintaining healthy positive relationships, is to novice teachers per se.